Genetics, Agriculture, and Biotechnology - Suza, Walter; Lee, Donald (Open textbook library., 2021)
This textbook provides an introduction to plant genetics and biotechnology for the advancement of agriculture. A clear and structured introduction to the topic for learners new to the field of genetics, the book includes: an introduction to the life cycle of the cell, DNA and how it relates to genes and chromosomes, DNA analysis, recombinant DNA, biotechnology, and transmission genetics.